Frontiers in science and technology - Yunus, Kamaruzzaman (IIUM Press, 2012)
The intention of Frontiers of Science and technology is to provide an absolutely introductory yet rather systematic and comprehensive textbook tailored to the interests of broader audience of science, technology, and medicine. This book is written by a number of active researchers of various scientific disciplines with varying level of research experiences in science which is mostly interdisciplinary and multidisciplinary in nature.